2003
DOI: 10.1103/physrevlett.90.055504
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Dynamics Simulations of Carbon Nanotubes as Gigahertz Oscillators

Abstract: Recently, Zheng and Jiang [Phys. Rev. Lett. 88, 045503 (2002)]] have proposed that multiwalled carbon nanotubes could be the basis for a new generation of nano-oscillators in the several gigahertz range. In this Letter, we present the first molecular dynamics simulation for these systems. Different nanotube types were considered in order to verify the reliability of such devices as gigahertz oscillators. Our results show that these nano-oscillators are dynamically stable when the radii difference values betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
287
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(311 citation statements)
references
References 12 publications
22
287
0
2
Order By: Relevance
“…as elements in nano-circuits [2], nano-oscillators [3], nanomagnets [4] and opto-electronic devices [1]. A similar rapid progress was also achieved in optics.…”
mentioning
confidence: 69%
“…as elements in nano-circuits [2], nano-oscillators [3], nanomagnets [4] and opto-electronic devices [1]. A similar rapid progress was also achieved in optics.…”
mentioning
confidence: 69%
“…Further studies, including mathematical models and molecular dynamics simulations, also predict frequencies in the gigahertz range. Legoas et al 8 observed frequencies as high as 38 GHz through molecular dynamics simulations. Liu et al 9 studied the oscillation of a C 60 fullerene inside a carbon nanotube using molecular dynamics simulations and confirmed the prediction of Zheng and Jiang 7 by observing a frequency as high as 74 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…1 This DWNT system should be useful for cylindrical molecular capacitors, GHz oscillators, nanocomposites, field emission sources, nanotube bicables, electronic devices, and other applications. [1][2][3][4] The control/tuning of the electronic properties of nanotubes is a key point for transforming their potential into realworld technology. One way for achieving this control/tuning is by carrying out donor or acceptor doping experiments where either electrons or holes are added to the carbon nanotube through intercalation and/or functionalization processes.…”
Section: Introductionmentioning
confidence: 99%